Distribusi Fungsi Di Antara Dramatik Persona Dalam Doyan Neda Perspektif Vladimir PROPP - Azis, Muhamad Sahril; Mahsun, Mahsun; Mahyudi, Johan (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to examine and describe the narrative structure of Doyan Neda's lontar. The focus of the analysis is on how the distribution of functions among dramatic personas in Doyan Neda through the action environment of Vladimir Propp's perspective. The method used in this research is descriptive qualitative. The source of data in this study is the Doyan Neda lontar translation. Collecting data using the read method accompanied by note-taking techniques. The analytical method is based on the constant comparative analysis method. This study reveals that the Doyan Neda lontar manuscript as old literature is not merely a story but a storytelling as well as a text whose nature and content is an event that has strong relevance to the Sasak people. This can be seen in the functions (actions of the characters) in the story which are distributed in the action environment.